Pengembangan Sumberdaya Wilayah Untuk Meningkatkan Ekonomi Desa Narimbang - Ananda Diah Oktaviani; Valyanisa Byzzanthi; Tita Nursyamsiah (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Utilization of natural resources in daily life for the welfare of mankind is not accompanied by the management and reuse of natural resources that have been wasted such as the presence of plastic waste, the presence of organic waste and others. Vertical garden is included in the form of indirect recycling of plastic bottle waste problem which means the use of used plastic bottles as the main component in the manufacturing of vertical garden. There are two activities carried out by the creation of vertical garden and activities Narimbang Youth Camp (NYC). A series of activities conducted in the form of socialization about garbage, family medicinal plants, how to create vertical garden and plant crops. Narimbang Youth Camp (NYC) is a socialization program about the importance of having an entrepreneurial spirit, creative thinking, and knowledge of digital marketing. Key words: Digital, natural resources, organic trash